A scoundrel of her own - Reid, Stacy (Reid, Stacy. Sinful wallflowers., 2022)
"Lady Ophelia Darby exists in two worlds. In one, she is the impudent, willful daughter of a powerful marquess and darling of the ton. In the other, she moves through the underworld's shadows as songstress Lady Starlight, protected only by the notoriously wealthy scoundrel Devlin Byrne. But when she stumbles upon her beloved father's darkest secrets, the line between her two worlds quickly blurs. Now she needs the help of the one man a lady should never trust."--Page 4 of cover.